Individual Sea Urchin Coelomocytes Undergo Somatic Immune Gene Diversification - Oren, Matan; Rosental, Benyamin; Hawley, Teresa S.; Kim, Gi-Young; Agronin, Jacob; Reynolds, Caroline R.; Grayfer, Leon; Smith, L. Courtney (Frontiers in Immunology, 2019)
Abstract The adaptive immune response in jawed vertebrates is marked by the ability to ‎somatically diversify specific immune receptor genes. Somatic recombination and hypermutation ‎of gene segments are used to generate extensive repertoires of T and B cell receptors. In contrast, ‎jawless vertebrates utilize a distinct diversification system based on copy choice to assemble their ‎variable lymphocyte receptors. To date, very little evidence for somatic immune gene ‎diversification has been reported in invertebrate species. Here we report that the SpTransformer ‎‎(SpTrf; formerly Sp185/333) immune effector gene family members from individual ‎coelomocytes from purple sea urchins undergo somatic diversification by means of gene ‎deletions, duplications, and acquisitions of single nucleotide polymorphisms. While sperm cells ‎from an individual sea urchin have identical SpTrf gene repertoires, single cells from two distinct ‎coelomocyte subpopulations from the same sea urchin exhibit significant variation in the SpTrf ‎gene repertoires. Moreover, the highly diverse gene sequences derived from single coelomocytes ‎are all in-frame, suggesting that an unknown mechanism(s) driving these somatic changes involve ‎stringent selection or correction processes for expression of productive SpTrf transcripts. ‎Together, our findings infer somatic immune gene diversification strategy in an invertebrate. ‎